Teenagers Resilience In Orphanage And Its Implications For Guidance and Counceling - Widya Permata Sari; Afrizal Sano (Universitas Negeri Padang, 2019)
The research was based on the condition of the teenagers in orphanages that lived without parent. They will surely encounter various obstacles and difficulties in dayli life. Then to handle these teenagers needed an ability called resilience. The purpose of this research is to describe the resilience of teenagers in Orphanage’s Shine Al-Falah Padang. The sampel in this research is 74 teenagers. The result of research showed that teenagers in orphan resilience by all aspect was in the high category. Teenagers orphan resilience seen from the aspect of emotion regulation, optimism, self-efficacy and reaching out was in the high category. And then, teenagers orphan resilience seen from the aspect impulsive control, causal analysis, and empati was in the medium category.